2021
DOI: 10.1002/1348-9585.12286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal discomfort among female cabin crew in Taiwan

Abstract: Objectives: This study investigated the prevalence of musculoskeletal discomfort among female cabin crew through cabin tasks and demographic factors, including age and seniority. Methods:This study conducted an online questionnaire survey targeted at female cabin crew in Taiwan and ensured that the sample size was with a statistical power of 0.95. This study evaluated the work intensity by ranking six common cabin tasks and examined musculoskeletal discomfort with Cornell Musculoskeletal Discomfort Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
2
4
1
Order By: Relevance
“…The common ergonomic risk factors for the crews identified in this study were awkward (bending and twisting) posture, working on standing, repetitive movements of the arms, and carrying loads. The poor working conditions, exposure to ergonomic hazards, and the MSDs suffered by the crews in this study were also evident in various other studies (Chen et al, 2021;Mulay et al, 2019;National Institute for Occupational Safety and Health, 2017). Furthermore, the current study revealed that the increasing age and flight duration were significant factors in the occurrence of MSDs among the crews, which was also found in previous studies (Khrisnapandit et al, 2016;Mulay et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The common ergonomic risk factors for the crews identified in this study were awkward (bending and twisting) posture, working on standing, repetitive movements of the arms, and carrying loads. The poor working conditions, exposure to ergonomic hazards, and the MSDs suffered by the crews in this study were also evident in various other studies (Chen et al, 2021;Mulay et al, 2019;National Institute for Occupational Safety and Health, 2017). Furthermore, the current study revealed that the increasing age and flight duration were significant factors in the occurrence of MSDs among the crews, which was also found in previous studies (Khrisnapandit et al, 2016;Mulay et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies also revealed the multisite occurrence of MSDs among the crews, which became a common health issue among the crews. In addition, the studies reported that the neck, shoulders, and low back were the common sites for MSDs (Chen et al, 2021;Ihlebaek and Rustad, 2022;Mulay et al, 2019;Mulyawan et al, 2021;Nur et al, 2018;Omholt, Tveito and Ihlebaek, 2017). Similarly, in the current study, a higher proportion of the participating crews were found to suffer from MSDs in the low back, shoulders, and neck.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations